MORPHOLOGICAL CHARACTERIZATION AND DENDROLOGICAL KEY OF FOUR FOREST SPECIES OF THE FACULTAD DE CIENCIAS AGRARIAS - UNIVERSIDAD NACIONAL DEL NORDESTE (FCA-UNNE) ARBORETUM - BIANCIOTTO, Virginia T. (2020)
In managed forests and plantations, misidentification of tree species in early life stages may have devastating ecological and economic impacts. Unfortunately, in some regions, dendrological keys of difficult to identify species have yet to be developed. We assessed dendrological characteristics of four tree species (Jacaranda mimosifolia, Peltophorum dubium, Enterolobium contortisiliquum and Delonix regia) within the Arboretum at the Facultad de Ciencias Agrarias - Universidad Nacional del Nordeste (FCA-UNNE), Corrientes, Argentina. All species share similar characteristics (e.g., leaves) during seedling and vegetative growth stages. Botanical samples of the trees were collected, photographed, and identified to species by comparing samples to herbarium specimens from the Instituto de Botánica del Nordeste (IBONE), Argentina. Our description of each species was based on morphological and organoleptic characteristics of the stem, branches, leaves, flowers, fruits, Diameter at Neck Height (DNH), bifurcation and health status. We also compiled information from the literature related to geographical distribution in Argentina, conservation status, and other relevant ecological information. These new species descriptions and dendrological keys may facilitate rapid and accurate field identification for ecologically and economically important tree species in early life stages when they appear to be morphologically similar.